Tamoxifen retinopathy: a case report - Wang, Lingling (Springerplus, 2015)
PURPOSE: To present a case of tamoxifen retinopathy on a 57-year-old woman. DESIGN: An observational case. METHODS: A review of history, clinical examination, and findings on Spectral-domain Optical Coherence Tomography (SD-OCT), fluorescein angiogram (FA) and electro-oculogram (EOG) was conducted. RESULTS: A 57-year old female patient, who had been treated with oral tamoxifen after mastectomy due to breast cancer, had profound visual impairment in both eyes. Disruption of the ellipsoid zone and interdigitation zone which represent photoreceptor damage as well as macular thinning was revealed on SD-OCT in both eyes. Bilateral retinal pigmented epithelium (RPE) function compromised was indicated by reduced Arden ratio in EOG. CONCLUSION: Tamoxifen-induced retinopathy could be detected by SD-OCT and EOG. As it is irreversible, patients who are given tamoxifen need regular ophthalmic consultation, including SD-OCT and EOG before and during the treatment in order to early detect and avoid further retinal damage.